ARABIC POETRY AS THE IDENTITY OF OUR SUSTAINABLE DEVELOPMENT - Asst. Prof. Dr. Waleed Jasim Al-Zubaidi (Scholars Digest Publishing, 2025)
Throughout human history, the humanities have held a status no less important than that of the applied sciences. In fact, they complement them, distinguished by their capacity to provide knowledge and arts that have benefitted other sciences and humanity at large. In this paper, we present a contribution that supports and complements other papers in fields such as engineering, medicine, and chemistry, reinforcing the collective effort to rescue the world and our planet through the goals of sustainable development. History, heritage, languages, and fine arts all possess ever-renewing visions, deeply rooted in the origins of our civilization. In this research paper, we identify Arabic poetry as the prevailing and leading force in our cultural arena—serving as a vessel for diverse sciences. Through poetry, knowledge has been transmitted via theoretical frameworks and foundational principles embedded in poetic compositions (arajiz) passed down orally across generations and later documented in writing. Arabic poetry is a profound medium for expressing emotions and sentiments, closely tied to nature and place. It vividly portrays mountains, rivers, meadows, forests, and flowers. Through Arabic poetry, we can promote environmental awareness, ecotourism, and foster a cultural identity for our communities. With the wealth of poetic and intellectual heritage we possess, alongside the ongoing contributions of contemporary generations in crafting poetry in various styles, we aim to inspire communities to engage with the environment in a modern, open-minded spirit—guided by the rhythm, rhyme, and structure of poetry, as well as its themes and hues that mirror the colors of flowers and the diverse features of our lands and climates. In this paper, we have endeavored to present a project that positions Arabic poetry as a core identity for our sustainable development and to open new doors in literary studies linked to environmental themes. And God is the source of success.
Keywords: Arabic Poetry / Sustainable Development / Nature / Identity / Water